Contrasting patterns of taxonomic, phylogenetic and functional variation along a Costa Rican altitudinal gradient in the plant family Melastomataceae - Kandlikar, Gaurav (2018)
The functional composition of plant communities in montane regions has been studied for decades, and most recent analyses find that environmentally favourable landscapes at lower altitudes tend to be dominated by species with resource-acquisitive traits, while more resource-conservative taxa dominate higher-altitude communities. However, it is unclear the extent to which this pattern is driven by co-gradient variation within clades or changes in clade representation across the gradient. To test for co-gradient variation, species composition, phylogenetic structure and functional traits were quantified for 97 species within the plant family Melastomataceae at five locations across a 2500- m altitudinal gradient along Volcán Barva in Costa Rica. Average melastome leaf force to punch, specific leaf area and leaf size vary with altitude, while four other functional traits do not. Taxonomic dissimilarity between communities was correlated with altitudinal difference, while phylogenetic dissimilarity was correlated with altitudinal dissimilarity only when measured with a metric that emphasizes shallow turnover of the tips of the phylogeny. These results highlight how species turnover may be more pronounced than functional or phylogenetic variation along altitudinal gradients. In addition, these results highlight the conservation value of lowland tropical forests, which here harbour a disproportionate amount of phylogenetic and functional diversity